Recovery of heart rate following intense dynamic exercise - Coote, J. H. (Experimental Physiology, 2010)
The Olympic biathlon is a very demanding physical event that requires high oxygen delivery, good cross-country skiing skills and skilful use of a rifle. Like all high-performance endurance athletes, high cardiac vagal tone is a characteristic and extends the range over which cardiac output can increase. In the biathlete, however, the enhanced vagal control of the heart also allows a strategy for better control of stability needed for accurately firing a rifle at the end of each lap of the race. The role of endurance training, central command, reflexes from muscle, and of the carotid-cardiac baroreceptor reflex in changing vagal tone during intense exercise and recovery is discussed.